Bacteria Contamination and Distribution in Patient Care Environment at Mbagathi Hospital Surgical and New-born Units - Magori, Enock Ongeri; Kang’ethe, Stanley Kamwati; Muna, Kennedy Kuria; Revathi, Gunturu; Omuse, Geoffrey (Annals of Pathology and Laboratory Medicine, 2021)
Background: Hospital environment can serve as an important reservoir and thus a critical element in the transmission of bacterial infections especially in critical care settings such as Surgical and new-born units. Contact with contaminated surfaces may lead to Hospital Acquired Infections (HAIs) among healthcare workers, visitors and patients. Further, HAIs may contribute to the spread of drug-resistant bacterial infections. This study sought to determine bacteriological characteristics and distribution in patient care environmental surfaces (Surgical and new-born units) at Mbagathi hospital Nairobi Kenya. Methods: A total of 700 samples were obtained from different surfaces: beds, bedside tables, sink taps handle, door handles, nursery incubators, paediatric weighing scale and new-born resuscitation machine by means of repeated screens over a period of three months. Microbiological isolation and identification were done by following standard laboratory methods established at Aga Khan University Hospital. Antibiotic susceptibility testing was carried out by using Vitek 2 system. Result: Five bacterial genera were isolated, S. Aureus was 3% (19/700), E. coli 0.9% (6/700), Acinetobacter species was 1.4% (10/700), Pseudomonas species 0.1% (1/700) and coagulase negative staphylococcus (CoNS)13.0% (88/700). Trimethoprim/Sulfamethoxazole and Benzylpenicillin were the most resistant antimicrobial agents while Oxacillin, Cefoxitin, Levofloxacin, Linezolid was most sensitive. Conclusion: All S. aureus were methicillin sensitive (MSSA). Patient beds surfaces were the most contaminated among the selected items while the nursery incubator was the least contaminated.